Ø§Ù„ØªØ±Ø§Ø¯Ù Ø¹Ù†Ø¯ Ø§Ù„Ù„ØºÙˆÙŠÙŠÙ† Ùˆ Ø§Ù„Ø£ØµÙˆÙ„ÙŠÙŠÙ† - Lubis, Torkis (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
Synonyms are words that have the same meaning in other words the same language. The language and the ushul fiqh have a view memorize the phenomenon of synonyms. The reality is that synonyms are found in Arabic, Al-Qur 'an and Al-hadith. Some experts view that it can be a word in the order of sentences replaced by synonyms, except da! am case of Al-Qur'an. Hi it's because the Qur'an, pronunciation and its meaning are Allah's revelations, read it worship.